A Comparative Study of Healthcare Professional Workload across Primary and Secondary Health Facilities - Sri Wahyuningsih Nugraheni; Nopita Cahyaningrum (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
The implementation of the Health Workload Analysis (ABK Kes) method reveals both strengths and weaknesses, particularly regarding the suboptimal execution of core tasks such as filing and distributing medical records. This study aims to compare the workload of health human resources (SDMK) between primary and advanced healthcare facilities—specifically Banyudono 1 Public Health Center and Indriati Boyolali Hospital—both of which have implemented hybrid medical record systems. Using primary data collected through interviews and observations and analyzed via the ABK Kes method, the results indicate a need for 10 additional staff members in the Casemix Unit at Indriati Boyolali Hospital and 2 additional medical record practitioners at Banyudono 1 Public Health Center. The Available Working Time (WKT) at the Public Health Center was set at 75,000 based on the Minister of PAN-RB Regulation No. 1 of 2020, whereas the Hospital used real-time calculations. While the Public Health Center aligns its policies with Ministry of Health Regulation No. 19 of 2020, the Hospital adjusts its staffing needs based on the ABK Kes results. Given that this method focuses primarily on quantity, future research and development (R&D) should integrate Lean Thinking for process analysis, ABK Kes for capacity, Queueing Theory for dynamic analysis, and NASA-TLX for psychological evaluation to provide a more holistic assessment of staffing needs.